2023
DOI: 10.1200/jco.22.01903
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Need for Adjuvant Therapy in Patients With Early-Stage Melanoma With Micrometastases

Abstract: Open Payments is a public database containing information reported by companies about payments made to US-licensed physicians (Open Payments).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Accordingly, we share some of Dr Hindié's 2 concerns regarding the use of SNB in the pT1b cohort and refer her to our recent parallel publication, which extensively analyzes this important topic. 4 We also agree with Dr Mangla 1 that current criteria for consideration of adjuvant therapy 5 are based mainly on interim outcomes of clinical trials 6,7 whose entry criteria used AJCC-7th edition staging and included routine completion lymphadenectomy after a positive SNB, a clinical practice no longer routinely undertaken. 8 Moreover, the primary end point of most randomized adjuvant therapy trials was recurrence-free survival, rather than overall survival or DSS—which are typically the focus of most prognostic studies such as ours.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Accordingly, we share some of Dr Hindié's 2 concerns regarding the use of SNB in the pT1b cohort and refer her to our recent parallel publication, which extensively analyzes this important topic. 4 We also agree with Dr Mangla 1 that current criteria for consideration of adjuvant therapy 5 are based mainly on interim outcomes of clinical trials 6,7 whose entry criteria used AJCC-7th edition staging and included routine completion lymphadenectomy after a positive SNB, a clinical practice no longer routinely undertaken. 8 Moreover, the primary end point of most randomized adjuvant therapy trials was recurrence-free survival, rather than overall survival or DSS—which are typically the focus of most prognostic studies such as ours.…”
mentioning
confidence: 72%
“…We read with interest the correspondence from Dr Mangla 1 and Dr Hindié 2 concerning our recent study, 3 which stratified patients with American Joint Committee on Cancer (AJCC)–8th edition stage IIIA melanoma into low-risk and high-risk subgroups on the basis of the sentinel node (SN) maximum tumor deposit size (MTDS). We found that MTDS ≥ 0.3 mm represented high-risk micrometastatic disease, whereas outcomes for patients with MTDS below that threshold were like those of SN biopsy (SNB)–negative patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Acral lentiginous melanoma has a higher percentage of positivity for KIT mutations, and drugs targeting KIT mutations like imatinib have been studied in metastatic settings. Their role in adjuvant treatment has not been established yet [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%